Efektivitas Senam Kaki pada Pasien Diabetes Melitus - Amelia, Putri; Wahyu Mashfufa, Erma (Jurnal Pustaka Keperawatan (Pusat Akses kajian Keperawatan), 2025)
This study aimed to determine the effect of diabetic foot exercise on improving foot sensitivity in a patient with diabetes mellitus in Pakis Village, Malang Regency. The research employed a quasi-experimental one-group pretest-posttest design involving a 60-year-old female patient with a seven-year history of diabetes. The intervention consisted of diabetic foot exercises performed for four weeks, three times per week. The monofilament test results showed an increase in sensitivity scores from 12 to 27 on the right foot and from 12 to 30 on the left foot, indicating improved peripheral sensory nerve function. These findings suggest that diabetic foot exercises enhance peripheral blood circulation, improve nerve impulse conduction, and stimulate plantar sensory receptors, resulting in increased foot sensitivity. Although this study involved only one participant, the results provide preliminary evidence that diabetic foot exercise is an effective, inexpensive, and easily applicable non-pharmacological intervention for preventing peripheral neuropathy complications in diabetic patients.